Developing a Conceptual Model for Da‘wah Literacy Index (DLI) - Choirin, Muhammad; Saoqi, Abdul Aziz Yahya; Sopa, Sopa; Abdul Kadir, Fakhrul Adabi; Mokhtar, Ahmad A'toa' Bin; Guleng, Marlon Pontino (Universitas Islam Negeri Mataram, 2024)
Da‘wah illiteracy has been the primary cause of the common practice of Islam in Indonesia. However, this issue needs to be addressed in academic works and the measurement of da'wah literacy. Therefore, this research aims to develop a model of the da'wah literacy index. This study employs qualitative content analysis approaches and focuses on group discussion to create a quantitative model. Furthermore, a quantitative method of Pearson and Cronbach Alfa is used to test the validity and reliability of the model. The developed measurement consists of 2 dimensions with ten variables and is measured by 39 indicators. The model validity test shows a p-value of less than 0.05, and the reliability test is more significant than 0.60. Thus, it indicates that the model is significantly valid and reliable. This research is theoretically important in the literature on Islamic studies, notably for understanding the measurement of da'wah literacy in Muslim society.